Understanding the knowledge about diabetic and its effect on eye among patients visiting a multi-specialty hospital: a cross-sectional study - Sharma, Shikha; Chander, Ashish; Yadav, Rakesh Kumar (International Journal Of Community Medicine And Public Health, 2024)
Background: The objective of this study was to access the knowledge about diabetic and its effect on eye. Methods: A cross-sectional study was conducted among 352 patients visiting a multi-specialty hospital of Moradabad, Uttar Pradesh. The study was conducted among the age group 29 to 80 years. A pre validated questionnaire was used to collect the responses about knowledge on diabetic and its effect on eye. Results: The study included a sample of 352 individuals aged between 29 and 80 years, with a mean age of 53.7 years. The gender distribution was fairly balanced, with 53.7% females and 46.3% males. Most participants resided in urban areas (60.8%), while the remaining 39.2% were from rural localities. Out of the 352 individuals surveyed, 282 participants, accounting for 80.1% of the total, indicated that they had heard of diabetic retinopathy. Out of the 352 individuals surveyed, 236 provided valid responses on asking diabetes affect eyes. Conclusions: Despite of good knowledge of participants about diabetic, eye health care providers must prioritize comprehensive education about the ocular complications of diabetes during routine consultations. Such interventions are crucial for early detection and management of diabetic eye diseases, which can significantly reduce the risk of vision loss and improve the quality of life for these patients.